Stress-induced epigenome changes as a risk factor in the onset of mental disorders - Shkarina, Liliia; Bozov, Kirill; Dzhauari, Stalik; Primak, Alexandra; Tkachuk, Vsevolod; Chaika, Yuliya; Neyfeld, Elena; Karagyaur, Maxim (Frontiers in Psychiatry, 2026)
The global mental health study has revealed a steady increase in the prevalence of mental disorders worldwide. This trend reflects not only the improvements in diagnostics but also the global population ageing and the intensification of negative environmental impacts that provoke the manifestation of such disorders. One of such primary external causes for mental disorders is stress, which accompanies humans throughout their lives. Stressful exposure, particularly chronic stress, can alter the expression of genes involved in the development, maturation, and functioning of the nervous system, which in turn may provoke the manifestation of mental disorders in susceptible individuals. The effects of stress can explain the increasing prevalence of mental illnesses (depression, anxiety disorders), and their aggravation with age. Stress seems to have the greatest impact during critical periods of brain development: intrauterine and early postnatal stages. The molecular mechanisms mediating the impact of stress on the expression of genes crucial for brain development and function, as well as the list of genes involved, remain poorly understood. In this review, we have attempted to summarize the known information on the influence of stress on the activity of epigenetic modifiers and the state of the epigenome, the expression of target genes, brain development, and changes in behavioral patterns. Studying such mechanisms and the genes involved opens up opportunities for diagnosing mental disorders at a new methodological level and potentially offers new precision approaches to their therapeutic correction at the epigenomic level.